2010
DOI: 10.1111/j.1600-0706.2010.18358.x
|View full text |Cite
|
Sign up to set email alerts
|

Interacting effect of wolves and climate on recruitment in a northern mountain caribou population

Abstract: There is limited research on the influence of Pacific‐based climate in large herbivore populations. Additionally, much of our understanding on the effect of large‐scale climate on ungulate population dynamics has occurred on forage‐limited rather than predator‐limited populations. We compared the influence of the Pacific Decadal Oscillation (PDO), North Pacific Index, and local weather on recruitment in a predator‐limited mountain‐dwelling caribou Rangifer tarandus caribou population in the Yukon Territory, Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 59 publications
1
23
1
Order By: Relevance
“…The young‐to‐adult female ratio is a composite measure of several demographic processes including survival of adult females, fertility, fecundity, and survival of young (Bonenfant et al ). Although the use of ratio data for inferring population dynamics has been criticized (Caughley , McCullough ), others have used these data for characterizing demographics of ungulate populations (Raithel et al ; Harris et al ; Hegel et al , ). If reproductive rates and survival of adult females remain high with little variation, age ratios can provide a reliable index to relative changes in λ, because variation in survival of young drives interannual changes in that metric (Gaillard et al , ; Raithel et al ; Harris et al ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The young‐to‐adult female ratio is a composite measure of several demographic processes including survival of adult females, fertility, fecundity, and survival of young (Bonenfant et al ). Although the use of ratio data for inferring population dynamics has been criticized (Caughley , McCullough ), others have used these data for characterizing demographics of ungulate populations (Raithel et al ; Harris et al ; Hegel et al , ). If reproductive rates and survival of adult females remain high with little variation, age ratios can provide a reliable index to relative changes in λ, because variation in survival of young drives interannual changes in that metric (Gaillard et al , ; Raithel et al ; Harris et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, estimating the nutritional capacity for survival or recruitment should provide a reference for the degree to which mortality is compensatory or additive relative to observed survival and recruitment. Indeed, studies have demonstrated positive effects of predator removal for ungulate populations that were not resource‐limited (i.e.,those in which predation had an additive effect; Gasaway et al , Kie and White , Gasaway et al , Hegel et al , White et al ), compared with those that were resource‐limited when predator removal had little effect (i.e., those in which predation was compensatory; Bartmann et al , Ballard et al , White et al , Hurley et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Although larger prey animals are more profitable, they may also cause a higher effort and risk of injury or death to the predator [10, 11, 12]. In addition, environmental conditions may also impact on the effort involved for the predator to encounter prey animals, and the efficiency by which the prey animal may escape an attack, i.e., their vulnerability [12, 13, 14]. …”
Section: Introductionmentioning
confidence: 99%
“…Among density-independent factors, weather conditions have significant and multidirectional effects on ungulate demography, operating mainly through changes in mortality or indirectly through the quantity and quality of food (Post and Stenseth 1999; Hone and Clutton-Brock 2007). For example, harsh winter conditions affected the survival rate of Soay sheep (Milner et al 1999; Coulson et al 2001), red deer ( Cervus elaphus ; Forchhammer et al 1998), and roe deer ( Capreolus capreolus ; Gaillard et al 1993), and they shaped recruitment in mountain-dwelling woodland caribou ( Rangifer tarandus caribou ; Hegel et al 2010). Autumn weather influenced reproduction rates of female white-tailed deer ( Odocoileus virginianus ), while spring weather conditions affected their reproductive success (Simard et al 2010).…”
Section: Introductionmentioning
confidence: 99%